The impact of in situ breast cancer and family history on risk of subsequent breast cancer events and mortality - a population-based study from Sweden. Issue 1 (December 2016) - Sackey, Helena; Hui, Miao; Czene, Kamila; Verkooijen, Helena; Edgren, Gustaf; Frisell, Jan; Hartman, Mikael
Abstract Background The clinical behavior ofin situ breast cancer is incompletely understood and several factors have been associated with invasive recurrence. The purpose of this study was to evaluate long-term risk of subsequent breast cancer and mortality among women diagnosed within situ breast cancer, in relation to family history Methods Using the population-based Swedish Multi-Generation and Cancer Registers we identified 8111 women diagnosed within situ breast cancer between 1980 and 2004. We used standardized incidence ratios (SIRs) to measure the relative risk of subsequent invasive or contralateralin situ breast cancer and standardized mortality ratios (SMRs) for relative risks of death. Results Among women diagnosed within situ breast cancer, the cumulative 10-year and 20-year risk for subsequent contralateral or ipsilateral invasive cancer was approximately 10 % and 18 %, respectively. The risk of subsequent invasive breast cancer was increased more than 4-fold (SIR 4.6 (95 % CI 4.2 − 4.9)) among women within situ breast cancer as compared to women in the general population and the risk of contralateralin situ breast cancer was increased almost 16-fold (SIR 16.0 (95 % CI 13.2–19.1)). Having a family history of breast cancer increased the risk of contralateral invasive breast cancer by almost 50 % (incidence rate ratio 1.5 (95 % CI 1.0–2.0)). Women under forty years old at diagnosis, without family history, had a 7-fold increased risk, and those with a family history had a 14-fold increased risk for subsequent invasive breast cancer with SIRs of 7.2 (95 % CI 4.8–10.5) and 14.3 (95 % CI 7.4–25.0), respectively. The overall risk of death in women within situ breast cancer was significantly increased by 30 % compared to the general population but was highly dependent on the occurrence of a second invasive cancer event (SMR 1.3 (95 % CI 1.2–1.4)). Conclusions Among women within situ breast cancer, a positive family history increases the risk of contralateral invasive breast cancer by almost 50 %. The risk of subsequent invasive breast cancer and mortality is substantially higher in younger women, which should be taken into account when planning their treatment and follow up.